1985
DOI: 10.1152/ajprenal.1985.248.4.f527
|View full text |Cite
|
Sign up to set email alerts
|

Localization of diuretic action in microperfused rat distal tubules: Ca and Na transport

Abstract: Experiments were performed in rats to examine the distal site of action of thiazide diuretics and the additive hypocalciuric properties of thiazides and amiloride. In clearance experiments, the maximal natriuretic and hypocalciuric dose of chlorothiazide was established. When amiloride was added, there was further augmentation of Ca reabsorption (P less than 0.025) but no additional natriuresis. Amiloride blunted thiazide-induced kaliuresis (P less than 0.001). Localization of the thiazide effect was studied i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 0 publications
1
66
0
Order By: Relevance
“…In addition, potassium may also be secreted apically by the renal outer medullary potassium channel (ROMK) and a potassium chloride cotransporter [133]. In addition, NCC modulates transcellular magnesium and calcium reabsorption in the DCT through interaction with the transporters TRPM6 and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 4 TRVP5, respectively (Figure 1) [16,85]. Only 5 to 10% of the filtered load of sodium is reabsorbed in the DCT and this is primarily mediated by NCC [23].…”
Section: Typical Hallmarks Of Nccmentioning
confidence: 99%
“…In addition, potassium may also be secreted apically by the renal outer medullary potassium channel (ROMK) and a potassium chloride cotransporter [133]. In addition, NCC modulates transcellular magnesium and calcium reabsorption in the DCT through interaction with the transporters TRPM6 and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 4 TRVP5, respectively (Figure 1) [16,85]. Only 5 to 10% of the filtered load of sodium is reabsorbed in the DCT and this is primarily mediated by NCC [23].…”
Section: Typical Hallmarks Of Nccmentioning
confidence: 99%
“…The unique ability of these agents to reduce renal calcium excretion, especially upon chronic administration, while simultaneously promoting that of sodium is a long-standing observation (1). Renal clearance (2), micropuncture (3)(4)(5)(6), and microperfusion (7,8) experiments identified the distal convoluted tubule as the nephron site at which thiazide diuretics inhibit sodium transport. Distal convoluted tubules are also the site at which thiazide diuretics stimulate calcium absorption (6).…”
Section: Introductionmentioning
confidence: 99%
“…Thiazide diuretics are known to have hypocalciuric action, probably resulting from their action on the distal nephron (Costanzo 1985). Shimizu et al (1991) reported that trichlormethiazide increases Ca2+ flux in the presence of PTH.…”
Section: Discussionmentioning
confidence: 99%